Digital Transformation of the Finance Function: A Systematic Literature Review of Automation, Analytics, and Organizational Effectiveness - Dessy Marhandrie (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
The digital transformation of the finance function has become a strategic priority for organizations seeking to improve operational efficiency, decision-making quality, and organizational effectiveness. This study aims to systematically review the existing literature on the roles of automation and analytics in transforming finance functions and creating organizational value. Using a qualitative Systematic Literature Review (SLR) approach based on the PRISMA 2020 framework, relevant peer-reviewed articles published between 2020 and 2025 were identified, screened, and synthesized from leading academic databases. The findings reveal that automation technologies, including Robotic Process Automation (RPA) and Artificial Intelligence (AI), primarily enhance process efficiency and accuracy, whereas business analytics significantly improves strategic decision-making, forecasting, and finance business partnering. Furthermore, successful digital transformation depends on organizational capabilities, digital leadership, governance, and employee competencies rather than technology adoption alone. The review also identifies key research gaps and provides theoretical and managerial implications for advancing finance function transformation and sustainable organizational effectiveness.